The Role of Body Mass Index, Hemogblobin Levels in Women Giving Birth to Neonatal Weight - Linda Yanuana Fanida Tantowi; Dita Pratiwi Kusuma Wardani; Kurniawan; Dewi Ambarwati (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Maternal nutritional status is monitored with BMI and is also one of the factors that have an impact during pregnancy. Poor nutrition before and during pregnancy leads to decreasing hemoglobin levels and low birth weight infants. This study aims to determine the correlation between hemoglobin levels and BMI of mothers giving birth to the weight of newborns at the Puskesmas Kebumen II, Kebumen District. This research used a retrospective study with medical record data collected from January to April 2022. This research involved 50 patient mothers giving birth at Puskesmas Kebumen II, Kebumen District. The data were analyzed by the Pearson correlation coefficient test. The results are BMI and newborn weight (p = 0.061, r = 0.367), hemoglobin levels, and newborn weight (p=0.852; r= -0.025). There was no correlation between BMI and hemoglobin levels to newborn weight at Puskemas Kebumen II, Kebumen District.